PRODUKTIVITAS DAN BIAYA ANGKUTAN TRUK DI TIGA KPH PERUMPERHUTANI, JAWA TENGAH - Dulsalam Apul Sianturi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
An investigation on truck hauling of logs has been carried out at three Perhutani Forest Districts in Central Java, in 1980, 1981 and 1982. The investigation comes to the following conclusions: Annual working days for gasoline trucks range from 689 to l,676 hours with an average of 1,240 hours, and that for diesel trucks from 671 to 811 hours with an average of 790 hours.Effective hauling output of gasoline iruchs in ton-km/year ranges from 9,833 to 65,482 with an average of 33,000, and that for diesel trucks from 6,683 to 108,948 with an average of 33,650.Hauling cost by gasoline truck in Rp per ton-km for the years 1980, 1981, 1982 increases from year to year, namely Rp 95, Rp 128 and Rp 169, and that by diesel truck Rp 78, Rp 80 and Rp 83, consecutively. Hauling cost by gasoline truck is higher than that by diesel truck.The highest component cost of hauling logging by gasoline truck is fuel, i.e. 43 percent, and that at diesel truck, spare parts, i.e. 62 percent